2020
DOI: 10.7759/cureus.10779
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Ketosis-Prone Diabetes in the Setting of COVID-19 Infection

Abstract: Diabetic ketoacidosis is typically associated with type I diabetes mellitus, but it can be associated with type II diabetes mellitus under the conditions of extreme stress or as a presenting manifestation of ketosis-prone type II diabetes mellitus. A 38-year-old prediabetic male presented to the emergency room with hyperglycemia six weeks after recovery from coronavirus disease 2019 (COVID-19) pneumonia. Laboratory results showed severe hyperglycemia, metabolic acidosis, positive ketones in urine and blood, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…New onset insulin-requiring diabetes in patients with COVID-19 has been reported in multiple studies and appears to persist after recovery from acute infection ( 118 , 120 , 121 , 122 , 123 ). Patients may present with severe hyperglycemia, including hyperosmolarity or ketoacidosis, or with milder hyperglycemia ( 124 , 125 , 126 , 127 ). Patients with more severe manifestations of acute COVID-19 appear to be at higher risk, with noted correlation between hypoxia and hyperglycemia among hospitalized patients without preexisting diabetes and prior to administration of glucocorticoid therapy ( 128 ).…”
Section: Resultsmentioning
confidence: 99%
“…New onset insulin-requiring diabetes in patients with COVID-19 has been reported in multiple studies and appears to persist after recovery from acute infection ( 118 , 120 , 121 , 122 , 123 ). Patients may present with severe hyperglycemia, including hyperosmolarity or ketoacidosis, or with milder hyperglycemia ( 124 , 125 , 126 , 127 ). Patients with more severe manifestations of acute COVID-19 appear to be at higher risk, with noted correlation between hypoxia and hyperglycemia among hospitalized patients without preexisting diabetes and prior to administration of glucocorticoid therapy ( 128 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, 6 weeks after recovery from COVID-19 pneumonia, he presented with DKA. His biochemical profile was consistent with type 2 diabetes as evidenced by normal C-peptide levels, and negative antibodies against islet cell, zinc transporter 8, insulin, and weakly positive anti-GAD antibodies [12]. Interestingly, on this second admission, his polymerase chain reaction (PCR) was negative for COVID-19 and his HbA1c value was 10.8% implying that blood glucose levels started to rise rapidly after the initial COVID-19 pneumonia 6 weeks earlier [12].…”
Section: Covid-19 As a Cause Of "New-onset" Type 2 Diabetesmentioning
confidence: 89%
“…To the best of the authors' knowledge, only one case report has provided some evidence that COVID-19 may cause new-onset type 2 diabetes [12]. Thus, Siddiki et al [12] described a 58 years-old man from Jamaica who initially presented with COVID-19 pneumonia. His HbA1c level during this initial presentation was 6.1%, i.e., in the prediabetes range [12].…”
Section: Covid-19 As a Cause Of "New-onset" Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…He quickly responded to oral anti-hyperglycaemic agents without addition of insulin. In difference all, except a few, reported patients with new-onset diabetes and ketosis/ketoacidosis had severe COVID-19 infection with presence of markedly elevated inflammatory markers [ [7] , [8] , [9] ] On review of literature only three cases, similar to our case, have been reported previously [ 10 ]. All the three cases had mild symptoms of COVID-19.…”
Section: Discussionmentioning
confidence: 99%